2020
DOI: 10.31436/imjm.v19i1.1333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Chlamydia Trachomatis and Other Sexually Transmitted Organisms in Infertile Couples Attending a Tertiary Medical Centre in Malaysia

Abstract: INTRODUCTION: Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV) and Mycoplasma genitalium (MG) infections are well recognized and prevalent sexually transmitted infections (STIs). The role of Mycoplasma spp and Ureaplasma spp are still controversial as some are commensals of genitourinary tract. OBJECTIVES: To estimate the prevalence rate of 7 organisms: Chlamydia trachomatis, Neisseria gonorrhoea, Mycoplasma genitalium, Trichomonas vaginalis, Mycoplasma hominis, Ureaplasma ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…15,23 Lower CT prevalence was observed in China (5.9%), Turkey (2.15%), Rwanda (3.3%), Jordan (3.9%), Argentina (5.3%), and Malaysia (7.3%). 21,[24][25][26][27][28] The higher prevalence rates were reported in Palestine (20.2%), Nigeria (28.0%), Netherlands (29.5%), Italy (31.8%), Iran (32.0%), and Tanzania (36.21%). [29][30][31][32][33][34] Studies from New Delhi, India observed also a higher prevalence of CT among infertile women than in current research (28.1% vs 15.6%).…”
Section: Discussionmentioning
confidence: 99%
“…15,23 Lower CT prevalence was observed in China (5.9%), Turkey (2.15%), Rwanda (3.3%), Jordan (3.9%), Argentina (5.3%), and Malaysia (7.3%). 21,[24][25][26][27][28] The higher prevalence rates were reported in Palestine (20.2%), Nigeria (28.0%), Netherlands (29.5%), Italy (31.8%), Iran (32.0%), and Tanzania (36.21%). [29][30][31][32][33][34] Studies from New Delhi, India observed also a higher prevalence of CT among infertile women than in current research (28.1% vs 15.6%).…”
Section: Discussionmentioning
confidence: 99%